Da anistia à redemocratização: o processo de esquecimento da 5ª Companhia de Guardas - COSTA, Carolina Silva da (Universidade Federal do Pará, 2023)
When talking about the dictatorship of 1964-1985, one goes back to a sensitive past, laden with memories and traumas that persist in power struggles, installed in the democratic process in Brazil since Law nº 314/1967 on National Security, passing through Law 6,683/1979 from Amnesty to the current historic buildings. Understanding and knowing the speeches and characters whose past lived is a study developed by researchers of the history of the present time, as well as problematizing the memory that permeates through subjective and also physical fields - the museums - places of memories brought by Nora (1988). Those spaces whose purpose is to remember, however, when they create a gap of forgetfulness, it becomes paradoxical, making it necessary to provoke historiographical constructions with regard to the dictatorial period. In this way, the methodology with bibliographical analysis was used in articles, books and productions, which cited the 5th Company of Guards as a place of prison, today Museum of Contemporary, Modern Art and photos, or House of Eleven Windows, located in the neighborhood of Cidade Old woman in Belém–PA. Museum that makes up one of the formative spaces of Happy Lusitânia, the set of heritage revitalized and resignified within the project that aims to publicize the first contacts of the European colonizer and the natives. House of Eleven Windows, in its chronological functions, served as the home of Domingos Bacelar, then as a Military Hospital and a space for the collection of testimonies and incarcerations of subversives in the 20th century, the 5th Company of Guards and finally the Museum. However, the point of discussion of this research is that in its current curatorial proposal, its repressive past is not disclosed, leaving the visitor out of tune with the real history contained in general, since not even all passivity passed on actually occurred in this space. Therefore, gathering in this research a historiographical base of names identified as subversive, in their actions within the resistance and that were sent to provide clarifications in the 5th Company of Guards, is the objective of this research, with the intention of provoking the sensitive memory in opposition to the speeches implanted by the silence and oblivion built in the building.